A Descriptive Study to Assess the Availability, Awareness, and Implementation of Workplace Safety Policies in Kanpur (International Journal of Food and Nutritional Sciences, 2025)
Abstract Introduction: This descriptive study assessed the availability, awareness, and implementation of workplace safety policies in Kanpur, India. Despite the significant occupational health risks associated with cold environments in manufacturing, systematic research on prevention remains limited in this sector.